2021
DOI: 10.1093/plcell/koab077
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequence assembly: a technical evaluation in barley

Abstract: Sequence assembly of large and repeat-rich plant genomes has been challenging, requiring substantial computational resources and often several complementary sequence assembly and genome mapping approaches. The recent development of fast and accurate long-read sequencing by circular consensus sequencing (CCS) on the PacBio platform may greatly increase the scope of plant pan-genome projects. Here, we compare current long-read sequencing platforms regarding their ability to rapidly generate contiguous sequence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
321
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 247 publications
(324 citation statements)
references
References 70 publications
2
321
1
Order By: Relevance
“…Since similar methodologies were used by our and previous studies ( Andersen et al, 2016 ; Habachi-Houimli et al, 2018 ), the result suggested that the great difference of NLR gene numbers in barley identified in the present study and previous studies should be caused by genome assembling issues of the short-read sequence strategy. This is in accordance with the result of a recent study, which showed that the updated barley genome has more NLR genes at the MLA locus than the early version genome assembly ( Mascher et al, 2021 ). Furthermore, the wide distribution of barley NLR genes on the phylogeny that constructed with NLR genes from T. urartu and A. thaliana suggested that NLR gene diversity in barley is also comparable with those in T. urartu .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Since similar methodologies were used by our and previous studies ( Andersen et al, 2016 ; Habachi-Houimli et al, 2018 ), the result suggested that the great difference of NLR gene numbers in barley identified in the present study and previous studies should be caused by genome assembling issues of the short-read sequence strategy. This is in accordance with the result of a recent study, which showed that the updated barley genome has more NLR genes at the MLA locus than the early version genome assembly ( Mascher et al, 2021 ). Furthermore, the wide distribution of barley NLR genes on the phylogeny that constructed with NLR genes from T. urartu and A. thaliana suggested that NLR gene diversity in barley is also comparable with those in T. urartu .…”
Section: Discussionsupporting
confidence: 92%
“…The hexaploid wheat T. aestivum has over 2000 NLR genes due to recently occurred polyploidization, whereas the diploid wheat T. urartu has 537 NLR genes. However, by improving the barley genome with long-read sequence strategy, a recently study revealed that the NLR gene number in barley might have been underestimated ( Mascher et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations